A Decision Support System For Roof Tile SelectionUsing AHP In The Bedingin Roof Tile Industrial Center - Ryan Erlangga Ardiansyah; Jamilah (MEKAR : Journal Information System and Computer Application, 2026)
Selecting the appropriate roof tile based on house specifications and user preferences is often a challenge, especially when facing a wide variety of available products. This study aims to design and develop a web-based Decision Support System (DSS) to assist in selecting roof tiles at the Genteng Bedingin Industry Center in Ponorogo. The method used is the Analytic Hierarchy Process (AHP), which allows for pairwise comparison among criteria and subcriteria and evaluates consistency in decision-making. The system considers six main criteria: tile type, price, batten spacing, kluntung size, thickness, and ease of installation, with weights that can be adjusted directly by users. Usability testing using the System Usability Scale (SUS) method involving 15 respondents resulted in a score of 92.48%, indicating that the system is highly user-friendly and delivers logical, needs-based recommendations. This system has proven to be effective in providing accurate and relevant tile selection recommendations and has potential for broader industrial implementation.